Digitalization as a Factor of Increasing Investment Activity in the Tourism Industry - KALABUKHOVA, Galina Valentinovna; MOROZOVA, Olga Anatolievna; ONOKOY, Lyudmila Sergeevna; CHICHEROVA, Elena Yurievna; SHADSKAJA, Irina Gennad'evna (Journal of Environmental Management and Tourism, 2020)
The article is devoted to the study of digitalization as a factor of increasing investment activity in the tourism industry. The goals of tourism industry digitalization are not clearly defined, coordinated by priority, or checked for the possibility of their implementation. Therefore, it is important to formulate the real investment goals from the formal goals with the establishment of specific targets. The development of digital technologies can have a profound impact on investment in the tourism industry. Travel companies must use technologies such as social networks, mobile, analytics, and embedded devices to change customer interaction, internal operations, and even their investment models. In this case, the greatest economic impact in the tourism industry is provided by the transition to digital processes and the introduction of digital technologies within the value chains.